Explore BrainMass

Explore BrainMass

    Algebra Help

    Not what you're looking for? Search our solutions OR ask your own Custom question.

    This content was COPIED from BrainMass.com - View the original, and get the already-completed solution here!

    Solve by graphing. Indicate whether each system is independent, dependent or inconsistent.
    1. y= 2x-1
    x+y= 2

    2. 2x-3y=12
    3y-2x= -12
    3. 3x-y=4
    3x-y=0

    Solve each system by the substitution method. Indicate whether each system is independent, dependent or inconsistent
    4. x-y=3
    3x-2y=3

    5. 3y=x+5
    3x-9y= -10
    6. x=1/8y -1
    y=1/4x +39

    Solve by the addition method. Indicate whether each system is independent, dependent or inconsistent.
    7. -3x+y=3
    2x-3y=12

    8. x+3(y-1)=11
    2(x-y) +8y=28

    9. 1/3x - 1/6y = 1/3
    1/6x +1/4y= 0

    Solve each compound inequality. State the solution set using interval notation and graph it

    10. x&#8804; 0 and x - 6< 3
    11. 1/3x >2 and 1/4x>2
    12. -1/2x<6 or 2/3x<4
    Solve each absolute value equation and graph the solution set
    13. &#9474;x/2&#9474;-5= -1

    14. &#9474;2x-8&#9474;=0

    Solve each absolute value inequality and graph the solution set.

    15. &#9474;5x-1&#9474;&#8804; 14
    16. 1> 1/2&#9474;6- x &#9474;-3/4

    Graph each compound or absolute value inequality

    17. x + y &#8804; 1 or y &#8804; 4
    18. &#9474;x-3y&#9474;&#8805;9

    © BrainMass Inc. brainmass.com March 4, 2021, 7:24 pm ad1c9bdddf
    https://brainmass.com/math/basic-algebra/algebra-help-98472

    Solution Preview

    Solve by graphing. Indicate whether each system is independent, dependent or inconsistent.

    1. y= 2x-1 and x+y= 2

    The system is independent. x = 1 and y =1.

    2. 2x-3y=12 and 3y-2x= -12

    The system is dependent.

    3. 3x-y=4 and 3x-y=0

    The system is inconsistent.

    Solve each system by the substitution method. Indicate whether each system is independent, dependent or inconsistent
    4. x-y=3 and 3x-2y=3

    x = y + 3
    3x - 2y = 3
    3(y + 3) - 2y =3
    3y + 9 - 2y =3
    y = -6
    x = -3
    There is only one ...

    Solution Summary

    This solution is comprised of a detailed explanation to solve by graphing, the substitution method, addition method, indicate whether each system is independent, dependent or inconsistent, solve compound inequality and graph the solution set, and graph each compound or absolute value inequality.

    $2.49

    ADVERTISEMENT